Beberapa Cara Pemberian dan Tingkat Konsentrasi Em-4 terhadap Pertumbuhan Bibit Kakao (Theobroma cacao L.) - Erida Nurahmi; Yuswar Yunus; M. Ilham Tasbih (Jurnal Agrista, 2009)
Some Ways Application and Level EM-4 Concentration on Growth Seed Cacao (Theobroma cacao L.)ABSTRACT. Crop productivity is strongly influenced from the seed which will produce plants vigor and healthy. Efforts to get a healthy cacao seedling and various treatments which required strong support in creating an optimal environment to grow. One of these efforts is to use the potential of soil microorganisms endemic in growing media through the application of bio-activator (microorganisms) of land. This study aims to determine how and concentration of appropriate gifts in order to obtain good growth of cocoa seedlings and to determine whether there is linkage between these two factors tested. The design used was randomized block design with factorial pattern. 3x3 and 3 replications, so there are 27 units experiment. There are two factors studied, namely the factor for granting the solution of EM-4 (C) consist of 3 levels, and concentration factor of EM-4 (K) consisting of 3 levels. The result showed that the influence of the method of solution of EM-4 is only significant effect on high-added cocoa seedling age of 60 and 70 DAT. The way of EM-4 is best through the soil only. While on the other variables had no significant effect. While the EM-4 solution concentration significantly affected the height increment of seedling of cocoa age of 70 DAT. The best concentration of EM-4 was 5 ml/l of water. In addition to higher seed, the concentration tested did not significantly effect other variables. There was no significant interaction between the route of administration with a concentration of EM-4 for all variables observed the growth of cocoa seedling.